Pengaruh Ferrite Bead Terhadap Performa Mesin Honda Supra FitIT 100 CC - Masruri, Thohir, Ir. Sartono Putro, MT (2017)
Ferrite Bead is a ceramic compound made from iron oxide powder that have high electrical resistivity so able to minimise electromagnetic interference that causes a decrease in energy and electrical system tools function. The use of ferrite bead mounted on wires spark plug ignition system engine gasoline 4 stroke. The goal of the research is mounting ferrite Bead to get influence on performance of gasoline engine 4 stroke, with premium fuel, pertalite and builtin. Engine performance include power, torsi, kbbs and acceleration of the engine. The results obtained from this research is mengingkatnya engine performance due to the installation of a ferrite bead on the ignition system of the engine 4 stroke data acquisition, with no premium increase on power 1.5%, 0.3%, torque and Acceleration time 2.80% and the efficiency of the SFC amounted to 13%. Then on the pertalite experience an increase in torque 0.50%, 2.2% and accelerated the time as well as the efficiency of SFC of 10.5%. And then on the builtin gained an increase at 1% and accelerated time 2.2% as well as the efficiency of the SFC amounted to 10.2%. From the results of the data that the ferrite could affect gasoline engine ignition system 4 stroke is not to obtain a more perfect combustion thereby engine performance better. Keywords: Ferrite Bead, Petrol, efficiency, engine performance